Identification of novel antisense long non-coding RNA APMAP-AS that modulates porcine adipogenic differentiation and inflammatory responses - Lin-zhen ZHANG; Li HE; Ning WANG; Jia-hua AN; Gen ZHANG; Jin CHAI; Yu-jie WU; Chang-jiu DAI; Xiao-han LI; Ting LIAN; Ming-zhou LI; Long JIN (Journal of Integrative Agriculture)
Long non-coding RNAs (lncRNAs) are emerging as powerful regulators of adipocyte differentiation, fat metabolism and gene expression. However, the functional roles and mechanisms of lncRNAs in these processes remain unclear. Here, we identified a novel antisense transcript, named APMAP-AS, transcribed from adipocyte membrane-associated protein (APMAP) in the pig genome. APMAP-AS and APMAP were highly expressed in retroperitoneal adipose of obese pigs, compared with that in control pigs. Using a bone mesenchymal stem cells (BMSCs) adipogenic differentiation model, we found that APMAP-AS positively regulated adipogenic differentiation. APMAP-AS had the potential to form an RNA–RNA duplex with APMAP, and increased the stability of APMAP mRNA. Additionally, APMAP-AS promoted lipid metabolism and inhibited the expression of inflammatory factors. These findings of a natural antisense transcript for a regulatory gene associated with lipid synthesis might further our understanding of lncRNAs in driving adaptive adipose tissue remodeling and preserving metabolic health.